2018
DOI: 10.3389/fncel.2018.00122
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sevoflurane Exposure During Mid-Pregnancy on Learning and Memory in Offspring Rats: Beneficial Effects of Maternal Exercise

Abstract: Fetal exposure to general anesthetics may pose significant neurocognitive risks but methods to mitigate against these detrimental effects are still to be determined. We set out, therefore, to assess whether single or repeated in utero exposure to sevoflurane triggers long-term cognitive impairments in rat offspring. Since maternal exercise during pregnancy has been shown to improve cognition in offspring, we hypothesized that maternal treadmill exercise during pregnancy would protect against sevoflurane-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 52 publications
10
34
0
Order By: Relevance
“…Over an extended period, β-tubulin III was suppressed while GFAP remained overexpressed. The reduction of β-tubulin III indicates the number of neurons was reduced, which supports the same behavioral test results obtained in our previous research showing multiple exposures to sevo urane can lead to neurocognitive impairment and learning disability in the offspring (Wu et al, 2018). Assumedly, sevo urane causes premature differentiation of NSCs which result in neuronal damage in postnatal off-spring.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Over an extended period, β-tubulin III was suppressed while GFAP remained overexpressed. The reduction of β-tubulin III indicates the number of neurons was reduced, which supports the same behavioral test results obtained in our previous research showing multiple exposures to sevo urane can lead to neurocognitive impairment and learning disability in the offspring (Wu et al, 2018). Assumedly, sevo urane causes premature differentiation of NSCs which result in neuronal damage in postnatal off-spring.…”
Section: Discussionsupporting
confidence: 89%
“…Our previous study showed that a single maternal 3% sevo urane exposure does not cause long-term neurocognitive impairment in fetal rats, while repeated exposure of 3% sevo urane can cause learning and memory impairment in the offspring (Wu et al, 2018). The β-tubulin III and GFAP levels in rat brains were examined on postnatal day 28 ( Figure 4) as well as in the cultured NSCs ( Figure 5).…”
Section: Repeated Exposure To Sevo Urane Led To Early Differentiationmentioning
confidence: 97%
See 1 more Smart Citation
“…The brain tissues and collected cells were stored at -80°C before use and homogenized to determine protein expression using the western blotting protocol described in our previous study (Wu et al, 2018). The protein concentration was measured using the BCA Protein Assay Kit (P0010; Beyotime, China).…”
Section: Western Blotmentioning
confidence: 99%
“…Aberrant neural differentiation has been shown to contribute to cognitive impairment and neurogenesis inhibition in young and offspring rodents [34]. Sevoflurane regulates neurogenesis in offspring rats by down-regulated the expression of brain-derived neurotrophic factor (BDNF) that is the critical neural development and disease related gene [19,[35][36][37] and induces neurotoxicity and cognitive impairment in young mice [38,39]. But, the underlying mechanism by which sevoflurane regulates the expression of BDNF remains largely unknown, which impedes further research into anesthesia neurotoxicity in the developing brain.…”
Section: Introductionmentioning
confidence: 99%